SEXUAL DYSFUNCTION IN ALCOHOLICS- EXPERIENCE AT TERTIARY CARE CENTER OF NORTHEREN INDIA (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: The search for sex-enhancing drugs or aphrodisiacs has been a human fascination throughout history and alcohol being the most commonly and universally consumed substance, has been related to sexuality since time immemorial. Although alcohol may contribute to the initiation of sexual activity by subduing inhibitions and relieving anxiety,1 prolonged and heavy use can lead to alcohol-induced sexual dysfunction.2 Masters et al,3 proposed a four-phase human sexual response cycle – excitement, plateau phase, orgasm, and resolution which forms the basis for classifying various domains of sexual dysfunction in the latest Diagnostic and Statistical Manual of Mental Disorders-5 (DSM-5) as well as ICD-10.The relationship between alcohol and sexual dysfunction depends on a myriad of biopsychosocial factors. These include direct toxic effects of alcohol on the endocrine system, leading to derangements in the hypothalamo–pituitary–adrenal and the hypothalamo–pituitary–gonadal axis and neurotransmitters imbalance (increased GABA and reduced glutamate), psychosocial factors such as anxiety/ depression/ psychotropic medications, unemployment, illiteracy, poor socioeconomic status, and so on. Aim of study: To estimate prevalence of sexual dysfunction in Alcoholic Liver disease patients at tertiary care center of Northern India. Material and Methods: This study was conducted at Medical Gastroenterology Department at PGIMS, Rohtak. It was a prospective study done over two years, from 01.05.2025 to 30.04.2026, during which 200 confirmed alcoholic patients were enquired for any kind of sexual dysfunction. For better understanding 100 patients each of chronic hepatitis (F0-F3 fibrosis) and cirrhosis were enrolled. All 200 alcoholics were males, in 20-50 yrs age group and were sexually active. Patient with past history of sexual dysfunction, anxiety, depression, diabetes mellitus, hypertension, hypothyroidism, hepatitis B, C and HIV which can cause sexual dysfunction were not included in the study. All hepatitis patients were confirmed on daily intake of alcohol, biochemical tests include liver & renal function tests, complete hemogram, thyroid profile, blood sugar, HbA1C, Fibroscan, ultrasonogram and upper gastro-intestinal endoscopy. Fibrosis was graded by Fibroscan readings- 12.2 Kpa- F4 or cirrhosis. The written informed consent was taken before enrollment in the study. Observation and Results: Our department is seeing alcoholic liver disease (ALD) patients regularly for last 16 years and daily at least 10 ALD patients, including new and old come for consultation. All the biochemical tests, Fibroscan, ultrasonogram abdomen, Endoscopy, ultrasonogram abdomen and treatment are available free of cost which increases regular follow-up and compliance of patients. On prospective analysis of 200 confirmed ALD patients, all were males. Out of total pool of 200 patients, 100 patients each of F0-F3 fibrosis and cirrhosis were enrolled in the study. The sexual dysfunction was seen in 43 % of total ALD patients. Out of these 43 patients, 18 (41.86 %) were in F0-F3 and 25 (58.14 %) were having cirrhosis. Most common kind of sexual dysfunction was erectile impotence (36 patients, 83.72%) followed by and loss of libido (28 patients, 65.11%) and premature ejaculation (5 patients,11.62%). Out of total pool of 43 ALD patients with SD, characteristically, 23 patients (53.48 %) had both erectile impotence and loss of libido. Out of 100 patients of alcoholic cirrhotic patients, sexual dysfunction was seen in 25 patients (58.14 %) and out of them 21 (84 %) had erectile impotence and 3 (12 %) had premature ejaculation and 20 (71.42%) had loss of libido. In group of 100 patients of F0-F3 fibrosis with SD, total 18 patients (41.86 %) had sexual dysfunction. In them, 15 patients (83.33 %) had erectile impotence, 2 (13.33 %) had premature ejaculation and 8 (53.33 %) had loss of libido. Conclusion: In alcoholic patients, the main thrust of treating health care professionals goes on hepatic impairment and extra-hepatic manifestations are usually missed. Sexual dysfunction is important arm of extra-hepatic impact of alcohol which is rarely discussed by both doctor, patient and family members, most likely due to inhibition and male ego. Hence whenever treating an alcoholic, sexual history must be evaluated in detail and impact of same should be scientifically assessed and treated accordingly.